Investigating the Relationship Between on Public Expenditures on Government Performance – Panel Data Method, 1989-2019 - Ali Heydar Noori; Ahmad Sarlak; Mohammad Hossein Rahmati (پژوهش‌های برنامه و توسعه)
One of the most problematic issues in policymaking is the impact of government spending on its outcome. This paper collects extensive and unique data on government outlays and outcomes for various affairs for the period 1989-2019. Then this unique dataset is put to use to study the relationship between spending and outcome in panel data analyses. The fixed effect regression reveals that a one percent increase in spending on a chapter improves associated outcomes by 0,06 percent, however, the impact of two years lag is significant and about double the spontaneous effects. Nevertheless, the dynamic panel regression, by both Arrellano-Bond and Blundell-Bond approaches, shows that the lag in outcome is large, and it explains a large portion of dynamics. Moreover, the spontaneous impact of spending on the outcome is 0.01-0,03 percent. Therefore, to improve the outcome of spending, the government must plan for long-term expenditure instead of discretionary outlays.